2021
DOI: 10.1080/14760584.2021.1891889
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical emergence of poliovirus in 2020: part 2. exploration of the potential role of vaccines in control and eradication

Abstract: Objectives:The emergence of human pathogens with pandemic potential motivates rapid vaccine development. We explore the role of vaccines in control and eradication of a novel emerging pathogen. Methods: We hypothetically simulate emergence of a novel wild poliovirus (nWPV) in 2020 assuming an immunologically naïve population. Assuming different nonpharmaceutical interventions (NPIs), we explore the impacts of vaccines resembling serotype-specific oral poliovirus vaccine (OPV), novel OPV (nOPV), or inactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Current modeling for polio and performance of the GPEI to date provide relevant context about the actual situation [50,79]. In addition, for this hypothetical analysis, we implicitly assumed no availability of vaccines at the time of emergence, and we refer to a separate analysis that explores the potential impact of vaccines [80].…”
Section: Discussionmentioning
confidence: 99%
“…Current modeling for polio and performance of the GPEI to date provide relevant context about the actual situation [50,79]. In addition, for this hypothetical analysis, we implicitly assumed no availability of vaccines at the time of emergence, and we refer to a separate analysis that explores the potential impact of vaccines [80].…”
Section: Discussionmentioning
confidence: 99%
“…Western Australia's refuge policy can be interpreted as a success in the sense that it maintained near‐zero pathogen spread until the state was prepared to handle the spread and long after it was clear that the pandemic would not constitute an extreme global catastrophe. Prior research has found synergies between vaccines and nonpharmaceutical interventions such as refuges for the control of infectious diseases (Thompson et al., 2021b ). Western Australia's experience in COVID‐19 demonstrates the value of this approach.…”
Section: Postscript: January–april 2022mentioning
confidence: 99%
“…Many of her other favorite projects focus on variability and uncertainty in risk in support decision making (Thompson & Graham, 1996), value of information modeling (Thompson & Evan, 1997), dynamic modeling of a surprising paraoccupational risk (Thompson & Evans, 1993), the impact of variability on groundling risks (Thompson et al., 2001), and content analyses of entertainment media (Thompson & Haninger, 2001; Yokota & Thompson, 2000) marketed to children. A recent favorite applied the global polio model to ask the questions: What if polio emerged for the first time in late 2019 instead of COVID‐19 and what might we expect from vaccines (Thompson et al., 2021b, 2021c)?…”
Section: Favorite Projectsmentioning
confidence: 99%